Proteomic Profiling of the Interactions of Cd/Zn in the Roots of Dwarf Polish Wheat (Triticum polonicum L.) - Wang, Yi; Wang, Xiaolu; Wang, Chao; Wang, Ruijiao; Peng, Fan; Xiao, Xue; Zeng, Jian; Fan, Xing; Kang, Houyang; Sha, Lina; Zhang, Haiqin; Zhou, Yonghong (Frontiers in Plant Science, 2016)
Cd and Zn have been shown to interact antagonistically or synergistically in various plants. In the present study of dwarf polish wheat (DPW)roots, Cd uptake was inhibited by Zn, and Zn uptake was inhibited by Cd, suggesting that Cd and Zn interact antagonistically in this plant. A study of proteomic changes showed that Cd, Zn and Cd+Zn stresses altered the expression of 206, 303 and 190 proteins respectively. Among these, 53 proteins were altered significantly in response to all these stresses (Cd, Zn and Cd+Zn), whereas 58, 131 and 47 proteins were altered in response to individual stresses (Cd, Zn and Cd+Zn, respectively). Sixty-one differentially expressed proteins (DEPs) were induced in response to both Cd and Zn stresses; 33 proteins were induced in response to both Cd and Cd+Zn stresses; and 57 proteins were induced in response to both Zn and Cd+Zn stresses. These results indicate that Cd and Zn induce differential molecular responses, which result in differing interactions of Cd/Zn. A number of proteins that mainly participate in oxidation-reduction and GSH, SAM and sucrose metabolisms were induced in response to Cd stress, but not Cd+Zn stress. This result indicates that these proteins participate in Zn inhibition of Cd uptake and ultimately cause Zn detoxification of Cd. Meanwhile, a number of proteins that mainly participate in sucrose and organic acid metabolisms and oxidation-reduction were induced in response to Zn stress but not Cd+Zn stress. This result indicates that these proteins participate in Cd inhibition of Zn uptake and ultimately cause the Cd detoxification of Zn. Other proteins induced in response to Cd, Zn or Cd+Zn stress, participate in ribosome biogenesis, DNA metabolism, and protein folding/modificationand may also participate in the differential defense mechanisms.